Gasification - Higman, Chris (Elsevier/Gulf Professional Pub., 2003)
Annotation "Written for scientists and engineers who wish to gain a deeper knowledge of gasification methods, Gasification, Second Edition provides an in-depth view of current technologies for the gasification of coal, oil, gas, biomass and waste feedstocks. This new edition is expanded to include Integrated Gasification Combined Cycles (IGCC), pre-investment and retrofitting, and plant reliability, availability and maintainability (RAM). Fundamental chemistry and thermodynamics of partial oxidation of carbonaceous materials are covered along with gasification reactor design and hear recovery options, making this reference one of the most comprehensive ever published."--Jacket.
Keywords: Coal gasification.; elektronické knihy; electronic books